A new society established within AIChE and Industry 4.0 and the Digital Transformation. Issue 1 (2nd January 2020) - Rinker, Michael
Abstract: This is a commentary on AIChE's newly formed Advanced Manufacturing and Processing Society (AMPS) and the first conference that AMPS organized on Industry 4.0 and the Digital Transformation.